- #1
dba
- 32
- 0
Homework Statement
I need to simplify the boolean expression by algebraic manipulation as much as possible.
(a+b+c)*(a'+c)*(a'+b')
Homework Equations
+ stands for OR
* stands for AND (or no operator between variables)
' Stands for NOT
The Attempt at a Solution
I tried but I do not know if this is correct.
(a+b+c)*(a'+c)*(a'+b')
= [aa' + ac + ba' + bc + ca' + cc] * (a'+b') => aa'=0, cc=c
= [0 + ac + ba' + bc + ca' + c] * (a'+b') => c + bc = c
= [ac + ba' + ca' + c] * (a'+b') => c + ac = c
= [ba' + ca' + c] * (a'+b') => c + a'c = c not sure if that works
= [ba' + c] * (a'+b')
= ca' + cb' + a'a' + a'b' + ba' + bb' => a'a'=a', bb'=0
= ca' + cb' + a' + a'b' + ba' => factor out the last two a'
= ca' + cb' + a' + a'(b' + b) => b'+b=1
= ca' + cb' + a' + a' => a'+a'=a'
= ca' + cb' + a' => factor out a'
= a'(1+c) + cb' => 1+c = 1
= a+cb'
Thanks for any help!